Strategy Formulation for Railway Container Transport of PT KALOG - Anindhita, Audya; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract - Indonesia has a huge potential of logistics market. However, the performance of logistics in Indonesia is still lagging behind other countries. One of the factor is because of the dependency on trucking modes. PT.KALOG is a subsidiary of PT.KAI which is a railway freight logistics company that has an important role to help streamline the national logistics and help to reduce the utilization of truck. The logistic industry also become more tight with the emergence of the other railway operator. This research aim to formulate the strategy for PT.KALOG to improve its performance in order to become excel in this competition and make the logistic in Indonesia more effective.Â Keywords - Strategic Management, Strategy Formulation, Environmental Scanning, Railway Container Transport, Logistics